In Silico Modeling and Docking Studies on Methionine Sulfoxide Reductase A Protein: In Silico Modeling and Docking Studies on Methionine Sulfoxide Reductase A Protein - Gunda, Shravan Kumar (International Journal of Pharmaceutical & Biological Archive, 2019)
Alzheimer disease (AD) is a neurodegenerative disorder including continuously progressive cognitive and functional deficits as well as behavioral changes and is related with amassing of amyloid and tau depositions in the brain. Subjective side effects of AD most ordinarily incorporate deficits in short-term memory, executive and visuospatial dysfunction, and praxis. Mammalian methionine sulfoxide reductase A is encoded by a single gene and is found in both cytosol and mitochondria. Biologically active compounds from different plants have been used to treat various ailments. In the present study, mitochondrial peptide methionine sulfoxide reductase protein sequence from Homo sapiens was retrieved from UniProt and selected structure of the peptide methionine sulfoxide reductase from Escherichia coli (Protein Data Bank [PDB] id: 1FF3) was used as template. The homology model was developed by using Modeller 9.20 version. Molecular docking studies were performed using Autodock4.2. 20 natural compounds were docked against modeled protein. All the compounds exhibited good binding energy. Campesterol showed with lesser energy of âˆ’9.0 Kcal/mol.